2015
DOI: 10.1051/0004-6361/201526430
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid flux towards circumprimary habitable zones in binary star systems

Abstract: Context. So far, more than 130 extrasolar planets have been found in multiple stellar systems. Dynamical simulations show that the outcome of the planetary formation process can lead to different planetary architecture (i.e. location, size, mass, and water content) when the star system is single or double. Aims. In the late phase of planetary formation, when embryo-sized objects dominate the inner region of the system, asteroids are also present and can provide additional material for objects inside the habita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…For each binary configuration studied, the main source of impactors is located in the region R 2 . As already proved by Bancelin et al (2016), this region is the primary source of icy asteroids reaching the HZ for this configuration, as both orbital resonances overlap in the asteroid belt. Contrary to the previous case (SR ∈ HZ), the water distribution in the HZ follows the r A distribution and EPs located around 1.0 au, on circular motion, can interact with fewer icy asteroids than EPs located at larger semi major axes.…”
Section: Water Transport: Merging Approachsupporting
confidence: 67%
See 3 more Smart Citations
“…For each binary configuration studied, the main source of impactors is located in the region R 2 . As already proved by Bancelin et al (2016), this region is the primary source of icy asteroids reaching the HZ for this configuration, as both orbital resonances overlap in the asteroid belt. Contrary to the previous case (SR ∈ HZ), the water distribution in the HZ follows the r A distribution and EPs located around 1.0 au, on circular motion, can interact with fewer icy asteroids than EPs located at larger semi major axes.…”
Section: Water Transport: Merging Approachsupporting
confidence: 67%
“…We can also notice that the number of crossings is higher when the SR is located inside the belt (right panels). This was also pointed out by Bancelin et al (2016) and can be explained by possible overlaps of the SR with MMRs.…”
Section: Impact Modelingsupporting
confidence: 60%
See 2 more Smart Citations
“…Indeed, Bancelin et al (2015Bancelin et al ( , 2016 showed that SR can exist inside the main-belt analogues of certain binary stargiant planet configurations. When the SR lies in the asteroid belt it can overlap with MMRs and be responsible for a high rate of asteroids crossing the HZ and, therefore, for an enhanced impact rate and water transport to the HZ (Bancelin, in preparation).…”
Section: Interior Versus Exterior Giant Planetsmentioning
confidence: 99%